ASPECTOS EPIDEMIOLÓGICOS, CLÍNICOS E HISTOPATOLÓGICOS DE OSTEOSSARCOMA EM MENORES DE 20 ANOS EM UM CENTRO DE ASSISTÊNCIA DE ALTA COMPLEXIDADE EM ONCOLOGIA (CACON) MARANHÃO) - Mello, Francisco Amazonas de Assis (2006)
Osteosarcoma is a malignance soft tumor, more frequently in children, teenagers and young adults and it represents 20% of all kind of sarcomas. It was aimed to describe epidemiological aspects such as age, gender, location and to classify kinds of osteosarcoma according to histopathological diagnose and histological grading and to relate it with clinical stage TNM data. It was done an observing and descriptive study in 26 (twenty-six) patients with age less than 20 years old with osteosarcoma treated in a High Complexity Oncology Assistance Centre called Instituto de Maranhense de Oncologia Aldenora Bello since April of 1996 to April of 2006. Variables were compared to Brazilian population database denominated PNAD from the year of 2005. Clinical, histopathological and histological grading aspects supported data to tumor classification. It was analyzed report books from these 26 patients in which was observed that age had a variety from 5 to 20, 14 were from female gender (53,8%) and 12 (46,2%) from male gender; twenty had brown skin (76,5%), white skin (15,4%) and 14 (53,8%) has come from country side of Maranhão. Most prevalent tumor locality was left femur (42,3%). Among the 22 pacients with conventional osteosarcoma, 13 were (50,0%) the mix type, followed by telangiectasic (11,5%; 3/26) and periosteal (3,8%; 1/26). There was a predominance of histology grade III (high grade) with 65,4%; grade II (low grade) with 30,8%. According to TNM stage, 15 (57,7%) were T1NxM0 and 7 were T1NxM1a, clinical stage was predominantly IIA (57,6%) followed by IVA (30,7%). From 10 patients initially diagnosed with mestastatic disease when admitted, 8 (34,6%) had lung implantation. The type of ostesarcomas, even with same clinical stage, may present outcome and time of survival different from each other and it depends on tumor grading. The research performed in the High Complexity Centre of Oncology in São Luís Maranhão had shown that conventional tumor and the ones with high grade was the most predominant.